La identidad marcaria como fortalecimiento del proyecto social “Entreprenehur Artesanal” - Mena Salazar, Liliana del Roció (2023)
The present research work on the brand identity of the social project "Entrepreneur Artesanal" in the city of Latacunga and its strengthening, aims to establish the identity of the project through branding. The actions that are developed in this research help to create a brand, in the same way the guidelines that are implemented and developed during the analysis and identification of the qualities that the dissemination project possesses are contemplated. The technique of mnemonic cards was used, which served to retain fundamental aspects of the sources of documentary information and bibliographic sources. Likewise, the results obtained in the brief and focus group are the basis for the development of brand strategies.